Вплив вихідного стану біомаси та умов піролізу на властивості біовугілля, отриманого з відходів Miscanthus х giganteus - Pidlisnyuk, V.V.; Stefanovska, T.R.; Borysenko, L.I.; Klius, V.P.; Chetveryk, H.O.; Medkov, A.I.; Lisnyak, V.V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2025)
The influence of pyrolysis conditions and the initial biomass state of Miscanthus x giganteus on the properties of biochar as a final product of oxidative and dry pyrolysis was investigated. Miscanthus biomass chips and waste pellets as well as wood waste were tested as feedstocks. Miscanthus chips were obtained from biomass grown on agricultural or marginal soils. The feedstocks were processed into biochar by oxidative pyrolysis in specially designed “household” and “farmer’s” stoves and by dry pyrolysis in a muffle furnace. Higher pyrolysis temperatures (600–700 °C) resulted in biochar with higher specific surface area (SSA) but lower yield. A balance between yield and SSA was found at 600 °C for 30–40 minutes, making this condition ideal for high-porosity biochar suitable for adsorption applications. For soil improvement, oxidative pyrolysis biochar from Miscanthus pellets and wood waste is preferred due to its higher fixed carbon content. For adsorption-based applications, dry pyrolysis biochar from Miscanthus chips is better due to its higher SSA. For fuel applications, biochar from oxidative pyrolysis of wood waste and Miscanthus waste pellets are ideal due to the highest calorific values. Thermogravimetric analysis of Miscanthus chips heated in air showed a process involving dehydration, pyrolysis, and oxidation reactions, and revealed its stages, namely, dehydration at 50–140 °C, hemicellulose degradation at 230–360 °C, cellulose degradation at 285–380 °C, and slow lignin destruction at 200–700 °C. Miscanthus chips exhibit spontaneous combustion characteristics, with smoldering beginning at 204 °C and complete combustion at 333 °C. Biochars produced from Miscanthus feedstocks has lower dehydration temperatures than corresponding Miscanthus feedstock, and it loses 86.2–92 % of its weight during thermal processing. Biochar obtained from Miscanthus pellets has the highest moisture content, while biochar from Miscanthus chips is less hydrophilic. Thermal stability varies among biochar samples, with significant differences in weight loss patterns during pyrolysis and oxidation. These differences suggest structural variations, likely due to the feedstock composition and pyrolysis conditions. Prepared biochar has both hydrophobic and hydrophilic properties, which is confirmed by the presence of characteristic peaks of hydrophobic and hydrophilic groups in the FTIR spectra. In particular, FTIR spectroscopy indicates the presence of hydroxyl (–OH), carbonyl (C=O), carboxyl (–COOH), and methylene (CH2) groups in carbonization products derived from the structural components of biomass – cellulose, hemicellulose and lignin. It was found that the SSA values of biochar from Miscanthus pellets produced by oxidative pyrolysis and biochar from chips produced by dry pyrolysis are in accordance with the parameters recommended by the International Biochar Initiative and are 187 and 419 m2/g, respectively. It has been concluded that the production of biochar from Miscanthus pellets by oxidative pyrolysis requires minimal energy consumption per unit of product. Processing Miscanthus waste by converting it into biochar is a promising solution within the circular economy concept, as biochar derived from Miscanthus ? giganteus can be an effective additive that can help restore degraded soils through phytoremediation.